2013
DOI: 10.3390/ijerph10010375
|View full text |Cite
|
Sign up to set email alerts
|

Job Stress Across Gender: The Importance of Emotional and Intellectual Demands and Social Support in Women

Abstract: This study aims to analyse whether any differences exist between the genders with respect to the effect of perceived Job Demands, Control and Support (JDCS model) on how individuals reach high levels of job stress. To do this, the perceived risk of suffering an illness or having an accident in the workplace is used as an outcome measure. The study is based on the First Survey on Working Conditions in Andalusia, which has a sample of 5,496 men and 2,779 women. We carry out a multi-sample analysis with structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 48 publications
6
65
3
2
Order By: Relevance
“…Manufacturing footwear requires intense manual labor with psychological pressure for productivity (Guimaraes et al, 2014). These factors associated with interpersonal relationships and work conditions influence stress and musculoskeletal disorders (MSD) prevalence (Da Costa, 2010;Rivera-Torres et al, 2013;Nimbarte et al, 2012). Work-related stress is defined by the National Institute of Occupational Safety and Health as a result of an imbalance between the demands of work and capabilities/features/needs of the worker (National Institute, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Manufacturing footwear requires intense manual labor with psychological pressure for productivity (Guimaraes et al, 2014). These factors associated with interpersonal relationships and work conditions influence stress and musculoskeletal disorders (MSD) prevalence (Da Costa, 2010;Rivera-Torres et al, 2013;Nimbarte et al, 2012). Work-related stress is defined by the National Institute of Occupational Safety and Health as a result of an imbalance between the demands of work and capabilities/features/needs of the worker (National Institute, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the effect of role stress on job satisfaction was substantially stronger for female employees and supervisory employees than male employees and non-supervisory employees. Rivera-Torres et al (2013) investigated the effects of job stress across gender by studying the relative importance of emotional and intellectual demands and social support in women. They reported that applying the Job Demands, Control and Support technique in function of the gender could contribute to a bigger understanding of how to reduce the levels of job stress in men and women, helping the design of more effective policies in this area.…”
Section: Resultsmentioning
confidence: 99%
“…Gender is assumed as a significant factor determining the stress in workplace (Bickford, 2005;Gaur & Jain, 2013;Rivera-Torres, AraquePadilla, & Montero-Simó, 2013) and it is suggested that women feel negative impacts of stress more than men (Bickford, 2005;Rivera-Torres et al, 2013). However, in their leading study on gender differences in sales force, Monciref et al (2000) show that there is no difference of job stress among saleswomen and salesmen, and a recent research confirms this result (Mulki, Jaramillo, Goad, & Pesquera, 2015).…”
Section: Job Stressmentioning
confidence: 99%